Investigation of the different particle size dust releases from rigid filter candles during pulse-jet cleaning. (February 2022) - Luan, Xin; Ji, Zhongli; Liu, Longfei; Wang, Ruifeng
Rigid filters made of ceramic or metal are widely used to remove solid particles from hot gases at temperature above 260 °C in the petrochemical and coal industries. Pulse-jet cleaning of fine dust from rigid filter candles plays a critical role in the long-term operation of these filters. In this study, an experimental apparatus was fabricated to investigate the behavior of a 2050 mm filter candle, which included monitoring the variation of pressure dynamic characteristics over time and observing the release of dust layers that allowed an analysis of the cleaning performance of ISO 12103-1 test dusts with different particle size distributions. These results showed the release behavior of these dusts could be divided into five stages: radial expansion, axial crack, flaky release, irregular disruption and secondary deposition. The cleaning performance of smaller sized dust particles was less efficient as compared with larger sized dust particles under the same operating conditions primarily because large, flaky-shaped dust aggregates formed during the first three stages were easily broken into smaller, dispersed fragments during irregular disruption that forced more particles back to the filter surface during secondary deposition. Also, a "low-pressure and long-pulse width" cleaning method improved the cleaning efficiency of the A1 ultrafine test dust from 81.4% to 95.9%.